Criminological characteristics of sexual violence - Kipāne, Aldona (SHS web of Conferences, 2018)
The aim of the current article is to analyse the criminological aspect of sexual violence. Nowadays sexual assault has become a major social issue in many contemporary cultures. Sexual violence is a complex interdisciplinary issue, which includes several aspects psychological, judicial, medical, and other aspects. Sexual crime is an urgent problem with a high level of latency, most part of such crimes are not reported in crime statistics. Particularly, sexual violence against children is a serious problem for Latvia and the world. At present, there is a sharp increase in such crimes as a human trafficking or commercial sexual exploitation; as well as the number of sexual crimes against boys is rising. Expansion of criminal activity in the cyberspace has also increased.publishersversionPeer reviewe